Electrode Separators for the Next-Generation Alkaline Water Electrolyzers - Aili, David; Kraglund, Mikkel Rykær; Rajappan, Sinu C.; Serhiichuk, Dmytro; Xia, Yifan; Deimede, Valadoula; Kallitsis, Joannis; Bae, Chulsung; Jannasch, Patric; Henkensmeier, Dirk; Jensen, Jens Oluf (American Chemical Society, 2023)
Multi-gigawatt-scale hydrogen production by water electrolysis is central in the green transition when it comes to storage of energy and forming the basis for sustainable fuels and materials. Alkaline water electrolysis plays a key role in this context, as the scale of implementation is not limited by the availability of scarce and expensive raw materials. Even though it is a mature technology, the new technological context of the renewable energy system demands more from the systems in terms of higher energy efficiency, enhanced rate capability, as well as dynamic, part-load, and differential pressure operation capability. New electrode separators that can support high currents at small ohmic losses, while effectively suppressing gas crossover, are essential to achieving this. This Focus Review compares the three main development paths that are currently being pursued in the field with the aim to identify the advantages and drawbacks of the different approaches in order to illuminate rational ways forward.